Presternal cutaneous bronchogenic cyst: a rare case - Srivani, N.; Srujana, Syamala; Prasad, Rajendra; Krishna, L.; Kumar, O. Shravan (International Surgery Journal, 2016)
Cutaneous bronchogenic cysts are rare congenital anomalies arising from the ventral foregut that forms the respiratory system as a result of abnormal budding of the bronchial tree during embryogenesis between 4th and 6th weeks of gestation. In the majority of the cases, pre-operative diagnosis is difficult, and the diagnosis is usually a histopathological surprise. We report a case of cutaneous bronchogenic cyst of the presternal location, which presented as a subcutaneous nodule with a discharging fistula. Histopathology showed a cyst lined by respiratory type of epithelium and unusual presence of lymphoid follicles around the cyst wall.